European paganism : the realities of cult from antiquity to the Middle Ages - Dowden, Ken, 1950- (Routledge, 2000)
European Paganism provides a comprehensive and accessible overview of ancient pagan religions throughout the European continent. Before there where Christians, the peoples of Europe were pagans. Were they bloodthirsty savages hanging human offerings from trees? Were they happy ecologists, valuing the unpolluted rivers and mountains? In European Paganism Ken Dowden outlines and analyses the diverse aspects of pagan ritual and culture from human sacrifice to pilgrimage lunar festivals and tree worship. It includes:* a 'timelines' chart to aid with chronology* many qu.